Thermally conductive sheet and manufacturing method thereof

JP7629728B2Active Publication Date: 2025-02-14DAIKIN FINETECH LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020215249
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-02-14
Estimated Expiration
2040-12-24

AI Technical Summary

Benefits of technology

【0019】 本発明によれば、均一な厚みを有する熱伝導性シートおよびその製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629728000002
    Figure 0007629728000002
  • Figure 0007629728000003
    Figure 0007629728000003
  • Figure 0007629728000004
    Figure 0007629728000004
Patent Text Reader

Abstract

To provide a thermally conductive sheet having uniform thickness.SOLUTION: A thermally conductive sheet includes a resin sheet having a gap, a fluorine-containing elastomer arranged inside the gap, and a thermally conductive material. A method for producing a thermally conductive sheet includes the steps of: preparing a resin sheet having a gap; holding a fluorine-containing elastomer in the gap of the resin sheet; and press molding the resin sheet holding the fluorine-containing elastomer, in which at least one of the resin sheet and the fluorine-containing elastomer has a thermally conductive material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive sheet and a method for producing the same. [Background technology]

[0002] In order to efficiently release heat generated inside various devices and electronic devices to the outside, a thermally conductive sheet may be disposed between a heat generating body and a heat sink. In recent years, the temperature inside electronic devices has increased due to the high density and miniaturization of electronic devices, and sheets with higher heat resistance and thermal conductivity are required. Patent Documents 1, 2 and 3 propose thermally conductive sheets comprising a fluorine-containing elastomer having high heat resistance and a thermally conductive filler dispersed in the fluorine-containing elastomer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-140056 A [Patent Document 2] JP 2014-61617 A [Patent Document 3] JP 2015-67737 A Summary of the Invention [Problem to be solved by the invention]

[0004] Generally, the thermally conductive sheet has high adhesion to the heat generating body and the heat dissipating body, and the thinner it is, the better. In these cases, the heat flow rate between the heat generating body and the heat dissipating body increases according to Fourier's law, and the thermal transferability also improves. However, it is difficult to mold a thermally conductive sheet that is uniformly thin and has a large area with the compositions described in Patent Documents 1, 2, and 3.

[0005] The present invention has been made in consideration of the above problems, and has an object to provide a thermally conductive sheet having a uniform thickness and a method for producing the same. [Means for solving the problem]

[0006] According to the present invention, there is provided a thermally conductive sheet comprising a resin sheet having voids, a fluorine-containing elastomer disposed at least inside the voids, and a thermally conductive material.

[0007] In the present invention, the fluorine-containing elastomer is held in the voids of the resin sheet and is integrated with the resin sheet. Therefore, despite the inclusion of the fluorine-containing elastomer, the thermally conductive sheet obtained has a uniform thickness. This enhances the adhesion between the thermally conductive sheet and the heat generating body and / or the heat dissipating body. As a result, the thermally conductive sheet according to the present invention exhibits excellent heat transferability in addition to thermal conductivity. Furthermore, a thin thermally conductive sheet can be obtained.

[0008] Thermal conductivity is the phenomenon in which heat moves from a high temperature area to a low temperature area within an object. Thermal transfer is the phenomenon in which heat moves from a high temperature area to a low temperature area between two or more objects.

[0009] The thermally conductive material may include a particulate thermally conductive material, and at least a portion of the particulate thermally conductive material may be supported on the resin sheet.

[0010] The resin sheet may contain a resin material having a heat resistance of 150° C. or higher.

[0011] The resin sheet may be a fibrous structure.

[0012] The thermally conductive material may include a fibrous carbon material.

[0013] The fluorine-containing elastomer may be disposed so as to cover one of the main surfaces of the resin sheet, or may be disposed so as to cover both of the main surfaces.

[0014] The thermally conductive sheet may have a thickness of 0.05 mm or more and 1.0 mm or less.

[0015] The thermally conductive sheet is suitable for use in semiconductor manufacturing equipment.

[0016] The present invention also provides a method for producing a thermally conductive sheet, comprising the steps of preparing a resin sheet having voids, retaining a fluoroelastomer in the voids of the resin sheet, and press-molding the resin sheet with the fluoroelastomer retained, wherein at least one of the resin sheet and the fluoroelastomer comprises a thermally conductive material.

[0017] In the present invention, a resin sheet having voids is used, so that the fluorine-containing elastomer is held in the voids and integrated with the resin sheet, thereby obtaining a thermally conductive sheet having a uniform thickness.

[0018] In the step of preparing a resin sheet, a resin sheet carrying particulate thermally conductive material may be prepared. Effect of the Invention

[0019] According to the present invention, there is provided a thermally conductive sheet having a uniform thickness and a method for producing the same. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view showing a schematic diagram of a thermally conductive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a thermally conductive sheet according to another embodiment of the present invention. [Diagram 3] 1 is an enlarged cross-sectional view showing a portion of a thermally conductive sheet according to one embodiment of the present invention. [Figure 4] 1 is a flowchart showing a method for manufacturing a thermally conductive sheet according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Fluorine-containing elastomers have high heat resistance and are therefore suitable as materials for thermally conductive sheets. On the other hand, fluorine-containing elastomers have high melt viscosity and therefore do not spread easily even when molten. Therefore, it is difficult to mold fluorine-containing elastomers into sheets of uniform thickness. If the thickness of a thermally conductive sheet is not uniform, the adhesion between the thermally conductive sheet and the heat generating body and / or heat dissipating body is likely to decrease, making it difficult to obtain excellent thermal conductivity.

[0022] Furthermore, the fluorine-containing elastomer is molded into a sheet and then vulcanized by heating. When cooled after heating, the sheet may shrink and deform (e.g., bend). The deformation of the sheet also reduces the adhesion between the sheet and the heating element and / or the heat sink.

[0023] The heat flow rate Q, which is an index of thermal conductivity, is expressed by the following formula according to Fourier's law: The larger the heat flow rate Q, the better the thermal conductivity. Q = k × A × ΔT / d (Where k is the thermal conductivity of the thermal conductive sheet (W / m K), A is the contact area of ​​the thermal conductive sheet (m 2 ), ΔT is the temperature difference (K), and d is the thickness of the thermal conductive sheet (m).

[0024] As can be seen from the above formula, the thermal conductivity is greatly affected by the contact area between the thermal conductive sheet and the heat generating body and / or heat dissipating body, i.e., the adhesion between the two. The higher the adhesion of the thermal conductive sheet, the higher the thermal conductivity. Furthermore, the smaller the thickness d of the thermal conductive sheet, the higher the thermal conductivity.

[0025] In this embodiment, a resin sheet having voids is used together with the fluorine-containing elastomer. By disposing the fluorine-containing elastomer in the voids of the resin sheet, the fluorine-containing elastomer is integrated with the resin sheet. As a result, the thickness of the thermally conductive sheet becomes uniform. A thermally conductive sheet of uniform thickness has excellent adhesion to a heat generating body and / or a heat dissipating body, and therefore has excellent thermal conductivity.

[0026] The standard deviation of the thickness at any five points of the thermally conductive sheet according to this embodiment can be, for example, 0.020 or less. The standard deviation is preferably 0.015 or less. The any five points are set to be spaced apart from each other by 3 cm or more. The thickness of the thermally conductive sheet can be measured by a digital dial gauge (for example, Digimatic Indicator, manufactured by Mitutoyo Corporation). The thickness of the resin sheet can be measured in the same manner.

[0027] Since the fluorine-containing elastomer is integrated with the resin sheet, it is possible to obtain a thermally conductive sheet of various thicknesses depending on the thickness of the resin sheet. For example, a thin thermally conductive sheet of 0.3 mm or less can be obtained. According to the above-mentioned Fourier's law, the thinner the thermally conductive sheet, the better the thermal transfer. Furthermore, it is possible to obtain a thermally conductive sheet of a large area. The larger the area of ​​the thermally conductive sheet, the larger the contact area with the heat generating body and / or heat dissipating body can be. According to this embodiment, it is possible to obtain a thin, large-sized, and more uniform thermally conductive sheet, for example, 500 mm square and about 0.1 mm thick.

[0028] The resin sheet also regulates the shape of the thermally conductive sheet, thereby suppressing deformation of the thermally conductive sheet. In addition, the resin sheet makes it easier to suppress thermal expansion of the thermally conductive sheet. Furthermore, the resin sheet also improves the durability of the thermally conductive sheet.

[0029] [Thermal conductive sheet] The thermally conductive sheet according to this embodiment includes a resin sheet having voids, a fluorine-containing elastomer disposed at least inside the voids, and a thermally conductive material.

[0030] The thermal conductivity of the thermally conductive sheet is not particularly limited and may be appropriately set depending on the application. The thermal conductivity of the thermally conductive sheet may be, for example, 0.15 W / m·K or more, preferably 0.20 W / m·K or more, and more preferably 0.25 W / m·K or more. The thermal conductivity of the thermally conductive sheet can be calculated by multiplying the thermal diffusivity, the specific heat, and the density. The thermal diffusivity of the thermally conductive sheet is measured, for example, by the laser flash method. The specific heat of the thermally conductive sheet is determined, for example, by differential scanning calorimetry (DSC). The density of the thermally conductive sheet is determined, for example, by the Archimedes method.

[0031] The temperature at which the mass of the thermally conductive sheet changes by 1%, measured according to JIS K 7120 thermogravimetry (TG) method (hereinafter sometimes referred to as the heat resistance temperature in the TG method), is preferably 300° C. or higher, and more preferably 400° C. or higher. This makes it easier to suppress a decrease in thermal conductivity even when various devices equipped with the thermally conductive sheet are used continuously for long periods of time.

[0032] The thickness of the thermally conductive sheet is not particularly limited and is appropriately set according to the application. The thickness of the thermally conductive sheet may be, for example, 1.0 mm or less, or 0.5 mm or less. The thickness of the thermally conductive sheet may be, for example, 0.05 mm or more, or 0.1 mm or more. The thickness of the thermally conductive sheet is preferably 0.05 mm or more and 1.0 mm or less. The thickness of the thermally conductive sheet is the average value of thicknesses at any five points of the sample. It is desirable that the any five points are spaced apart by 3 cm or more.

[0033] The size of the thermally conductive sheet is not particularly limited and is appropriately set depending on the application, etc. The minor axis or diameter of the thermally conductive sheet may be 100 mm or more.

[0034] The lower the surface hardness of the thermally conductive sheet, the easier it is to improve the adhesion of the thermally conductive sheet. The higher the adhesion, the easier it is to improve the thermal transferability of the thermally conductive sheet. The Martens hardness of the surface of the thermally conductive sheet measured by the nanoindentation method in accordance with ISO 14577 is preferably 0.1 MPa or more and 20 MPa or less. The Martens hardness of the surface is measured by pressing an indenter into the surface of the thermally conductive sheet with a load of 10 mN.

[0035] The electrical conductivity of the thermally conductive sheet is not particularly limited and is appropriately set depending on the application. The electrical conductivity of the conductive thermally conductive sheet at 20° C. is, for example, 1.00×10 -6 S / m or more, and 1.00×10 -3 S / m or more is preferable, 1.00×10 -1 S / m or more is more preferable. The electrical conductivity is 1.00×10 -4 If it is less than S / m, it is measured according to JIS K 6911 and is 1.00 x 10 -4 For values ​​of S / m or more, it is calculated from the electrical resistivity measured in accordance with JIS K 7194.

[0036] The thermally conductive sheet may have voids. The voids in the thermally conductive sheet originate from the voids in the resin sheet and / or the pores in the fluorine-containing elastomer. However, from the viewpoint of sealing property and thermal conductivity, it is desirable that the porosity of the thermally conductive sheet is small.

[0037] A plurality of thermally conductive sheets may be laminated and used as the thermally conductive sheet. The configurations of the plurality of thermally conductive sheets may be the same or different. For example, a conductive thermally conductive sheet and an insulating thermally conductive sheet may be laminated.

[0038] The thermally conductive sheet according to the present embodiment has excellent thermal conductivity and heat resistance, and can be used in various devices and electronic devices that can reach high temperatures. In particular, the thin and large thermally conductive sheet is suitable for semiconductor manufacturing equipment. Examples of semiconductor manufacturing equipment include dicers that separate substrates, wafer etching equipment, wafer cleaning equipment, and wafer drying equipment. Specifically, the thermally conductive sheet is suitably disposed between a heat source and a heat sink, such as an electrostatic chuck that adsorbs and holds a substrate by electrostatic force.

[0039] (Resin sheet) The resin sheet has a plurality of voids (pores). The plurality of voids may be continuous or may be independent of each other. It is preferable that the plurality of voids are continuous in order to easily retain the fluorine-containing elastomer.

[0040] One or more resin sheets are arranged on the thermally conductive sheet. The multiple resin sheets may be of the same type or of different types.

[0041] The porosity of the resin sheet is not particularly limited. In order that the thermally conductive sheet can hold a sufficient amount of fluorine-containing elastomer, the porosity of the resin sheet may be, for example, 30% or more, and preferably 40% or more. The porosity of the resin sheet may be, for example, 95% or less, and preferably 90% or less.

[0042] The porosity of the resin sheet can be calculated by the following formula. Porosity (%) = 100 (%) × {1 - mass of resin sheet G (g) / (apparent volume of resin sheet V (cm 3 ) × density of the material constituting the resin sheet ρ (g / cm 3 ))}

[0043] The thickness of the resin sheet is not particularly limited and is appropriately set depending on the application, etc. The thickness of the resin sheet may be, for example, 1.0 mm or less, or 0.5 mm or less. From the viewpoint of strength, the thickness of the resin sheet is preferably 0.05 mm or more, more preferably 0.1 mm or more.

[0044] Examples of the resin sheet include porous bodies, foams, and fiber structures formed by materials containing resin. Porous bodies can be obtained by a phase separation method, a stretching method, an etching method, and the like. Among them, fiber structures are preferred because the porosity can be relatively easily controlled. In addition, the fiber structures can be easily subjected to various surface treatments (e.g., conductive treatment, antistatic treatment, etc.). Examples of the fiber structures include nonwoven fabrics, woven fabrics, and knitted fabrics. Among them, nonwoven fabrics are preferred.

[0045] The mass per unit area of ​​the fiber structure is not particularly limited. The mass per unit area of ​​the fiber structure is, for example, 20 g / m 2 More than 600g / m 2 The thickness of the fibers constituting the fiber structure is not particularly limited. The diameter of the cross section of the fibers constituting the fiber structure along the circumferential direction may be, for example, 10 μm or more and 200 μm or less.

[0046] The resin sheet material contains a resin and, if necessary, various additives. The resin sheet material may further contain a thermally conductive material. The resin may be 50% by mass or more, 70% by mass or more, or 80% by mass or more of the resin sheet material.

[0047] From the viewpoint of heat resistance, the resin sheet preferably contains a resin material with a heat resistance temperature of 150°C or more. Such a resin material is known as a so-called super engineering plastic. The heat resistance temperature of the resin material is preferably 200°C or more. The heat resistance temperature is a value measured, for example, according to the UL746B standard. In the UL746B standard, the heat resistance temperature is the temperature at which the initial physical property value is reduced by half when exposed to the atmosphere at a constant temperature for 100,000 hours.

[0048] Examples of super engineering plastics include fluororesins, polyphenylene sulfide (PPS), polysulfone, polyethersulfone, amorphous polyarylate, polyetheretherketone, polyimide, polyetherimide, and liquid crystal polymers. Among these, fluororesins are preferred because of their excellent heat resistance and radical resistance.

[0049] Examples of fluororesins include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkoxyethylene copolymer (PFA), perfluoroethylene-propene copolymer (FEP), polyvinylidene fluoride (PVDF), and ethylene-tetrafluoroethylene copolymer (ETFE). Among them, completely fluorinated perfluororesins such as PTFE, PFA, and FEP are preferred. Perfluororesins are particularly excellent in heat resistance. By using perfluororesins, it is possible to easily obtain a thermally conductive sheet that can be used at high temperatures, for example, at 200°C or higher, and even at 300°C or higher.

[0050] (Fluorine-containing elastomer) The fluorine-containing elastomer contributes to the heat resistance of the thermally conductive sheet. With regard to the heat resistance of the fluorine-containing elastomer, in a compression set test carried out in accordance with JIS K 6262, the temperature at which the compression set of the fluorine-containing elastomer reaches 80% (hereinafter, sometimes referred to as the heat resistance temperature in the compression set test) is preferably 250°C or higher, more preferably 280°C or higher. With regard to the heat resistance of the fluorine-containing elastomer, in a thermogravimetric measurement method (TG method) measured in accordance with JIS K 7120, the temperature at which the weight of the fluorine-containing elastomer changes by 1% (hereinafter, sometimes referred to as the heat resistance temperature in the TG method) is preferably 380°C or higher, more preferably 400°C or higher. This makes it possible to easily obtain a thermally conductive sheet that can be used even at high temperatures, for example, 200°C or higher, or even 300°C or higher.

[0051] The fluorine-containing elastomer is disposed at least inside the voids of the resin sheet. The fluorine-containing elastomer may be disposed so as to fill at least a portion of the voids, and may fill all of the voids.

[0052] The fluorine-containing elastomer may be disposed so as to cover at least a part of at least one of the main surfaces of the resin sheet in addition to inside the voids of the resin sheet, whereby the hardness of the main surface of the thermally conductive sheet becomes equivalent to that of the flexible fluorine-containing elastomer and lower than the hardness of the inside of the thermally conductive sheet, and thus adhesion is easily improved.

[0053] In particular, the fluorine-containing elastomer is preferably arranged so as to cover the entirety of one main surface of the resin sheet. In other words, it is preferable that an elastomer region that contains the fluorine-containing elastomer but does not contain the resin sheet is arranged on one main surface side of the thermal conductive sheet. In this case, the resin sheet is not exposed from one main surface side of the thermal conductive sheet.

[0054] In the above case, the resin sheet may be exposed from the other main surface of the thermally conductive sheet. Alternatively, the other main surface may be covered with a fluorine-containing elastomer to such an extent that the resin sheet is exposed from the other main surface of the thermally conductive sheet during use. This prevents the fluorine-containing elastomer from softening and adhering to the heat generating body and / or heat dissipating body during use in a high-temperature environment. This improves the peelability of the thermally conductive sheet, making it possible to remove the thermally conductive sheet smoothly while suppressing the generation of residues. In particular, in the semiconductor field, it is important not to make semiconductor manufacturing equipment a source of contamination of semiconductors. Therefore, a thermally conductive sheet that is less likely to generate residues is suitable for use in semiconductor manufacturing equipment.

[0055] The elastomer regions may be disposed on both main surfaces of the thermally conductive sheet. In this case, the hardness of both main surfaces of the thermally conductive sheet becomes equivalent to that of the flexible fluorine-containing elastomer and is lower than the hardness of the inside of the thermally conductive sheet. Therefore, the adhesion between the thermally conductive sheet and both the heat generating body and the heat dissipating body is improved, and further improvement in heat transfer can be expected.

[0056] The thickness of the elastomer region is not particularly limited, and may be such that the resin sheet is not exposed from the main surface side on which the elastomer region is disposed, or such that the resin sheet is not exposed from the other main surface side of the thermally conductive sheet during use. The thickness of the elastomer region may be, for example, about 1 / 20 to 3 / 4 of the total thickness of the thermally conductive sheet, and preferably 1 / 10 to 1 / 2. Specifically, the thickness of the elastomer region may be 10 μm to 200 μm, and preferably 20 μm to 150 μm. The thicknesses of the elastomer regions disposed on both main surfaces of the thermally conductive sheet may be the same or different.

[0057] When an area having a constant thickness of 10 μm or more and containing a fluorine-containing elastomer but not a resin sheet is formed on at least one of the main surfaces of the thermally conductive sheet, the fluorine-containing elastomer may be regarded as being arranged so as to cover at least one of the main surfaces of the resin sheet.

[0058] The thickness of the elastomer region is determined from a cross section of the thermal conductive sheet in the thickness direction. First, a straight line is drawn through any point on the cross section, along the thickness direction of the thermal conductive sheet. Of these straight lines, the length of the shortest line segment from the resin sheet to the main surface of the thermal conductive sheet is measured. The length of this line segment is the thickness of the elastomer region.

[0059] The elastomeric region preferably further comprises a thermally conductive material, which further improves thermal conductivity.

[0060] In the thermal conductive sheet, the fluorine-containing elastomer may be crosslinked or may not be crosslinked. From the viewpoint of mechanical strength, the fluorine-containing elastomer is preferably crosslinked in the thermal conductive sheet. The fluorine-containing elastomer may have voids inside.

[0061] The amount of the fluorine-containing elastomer is not particularly limited. The proportion of the fluorine-containing elastomer in the thermal conductive sheet may be 20% by mass or more, and preferably 40% by mass or more. The proportion of the fluorine-containing elastomer may be 80% by mass or less, and preferably 60% by mass or less.

[0062] The fluorine-containing elastomer is not particularly limited, and examples of the fluorine-containing elastomer include those described in Japanese Patent No. 6463474.

[0063] The fluorine-containing elastomer may be a partially fluorinated elastomer or a perfluoroelastomer. Among them, perfluoroelastomers are preferred from the viewpoint of heat resistance. The perfluoroelastomer may further contain a cyano group (-CN).

[0064] Examples of partially fluorinated elastomers include vinylidene fluoride (VdF)-based fluororubber, tetrafluoroethylene (TFE) / propylene (Pr)-based fluororubber, tetrafluoroethylene (TFE) / propylene / vinylidene fluoride (VdF)-based fluororubber, ethylene / hexafluoropropylene (HFP)-based fluororubber, ethylene / hexafluoropropylene (HFP) / vinylidene fluoride (VdF)-based fluororubber, and ethylene / hexafluoropropylene (HFP) / tetrafluoroethylene (TFE)-based fluororubber.

[0065] An example of the perfluoroelastomer is a perfluoroelastomer containing tetrafluoroethylene (TFE) as a raw material monomer.

[0066] (Thermal Conductive Materials) The thermally conductive material provides thermal conductivity to the thermally conductive sheet. The thermal conductivity of the thermally conductive material is not particularly limited. The thermal conductivity of the thermally conductive material may be a value that makes the thermal conductivity of the thermally conductive sheet, for example, 0.15 W / m·K or more. From the viewpoint of heat dissipation, the thermal conductivity of the thermally conductive material is preferably 10 W / m·K or more, and more preferably 50 W / m·K or more.

[0067] The content of the thermally conductive material is not particularly limited. From the viewpoint of thermal conductivity, the total amount of the thermally conductive material may be 0.1 mass% or more of the thermally conductive sheet, and preferably 1 mass% or more. From the viewpoint of adhesion, the total amount of the thermally conductive material may be 50 mass% or less of the thermally conductive sheet, and preferably 30 mass% or less.

[0068] The form of the thermally conductive material is not particularly limited. For example, the thermally conductive material may be a coating that at least partially (preferably entirely) covers the surface of the resin sheet, or may be particulate. In particular, it is preferable that the thermally conductive material contains a particulate thermally conductive material (hereinafter referred to as a thermally conductive filler) in that the increase in hardness of the thermally conductive sheet is easily suppressed.

[0069] The thermally conductive filler may be supported on a resin sheet. Since the resin sheet is the skeleton of the thermally conductive sheet, when the thermally conductive filler is supported on the resin sheet, a path for heat transfer is easily formed with a small amount of the filler. As described above, it is important not to make the semiconductor manufacturing equipment a source of contamination of the semiconductor. Therefore, a thermally conductive sheet in which the amount of the thermally conductive material used is reduced is suitable for use in the semiconductor manufacturing equipment. The thermally conductive filler may be dispersed in a fluorine-containing elastomer. In this case, since a large amount of the thermally conductive filler can be dispersed, the thermal conductivity is easily improved.

[0070] The manner in which the thermally conductive filler is supported on the resin sheet is not particularly limited. The thermally conductive material may be added externally or internally to the resin sheet. More specifically, the thermally conductive filler may be attached to the surface of the material (typically a resin material) forming the resin sheet, or the thermally conductive filler may be contained inside the material forming the resin sheet, or both may be used. By adding the thermally conductive filler to the material forming the resin sheet and then forming it into a resin sheet, the thermally conductive filler can be contained inside the material. Among these, it is preferable that the thermally conductive filler is attached to the surface of the material forming the resin sheet. This makes it easier for the thermal conductivity and electrical conductivity of the thermally conductive sheet to be high.

[0071] The thermally conductive filler may be supported on the resin sheet and dispersed in the fluorine-containing elastomer, in which case the thermal conductivity can be improved while the total amount of the thermally conductive filler is reduced.

[0072] The material of the thermally conductive filler is not particularly limited. Examples of the material of the thermally conductive filler include metals, ceramics, and carbon materials. The thermally conductive filler is appropriately selected depending on the application. When both thermal conductivity and electrical conductivity are required, for example, a thermally conductive filler formed of a metal and / or an electrically conductive carbon material is selected. When both thermal conductivity and electrical insulation are required, for example, a thermally conductive filler formed of a ceramic is selected.

[0073] Examples of metals include silver, copper, aluminum, nickel, iron, and alloys thereof. Examples of ceramics include oxides, carbides, nitrides, and borides of metal elements, semimetal elements, and nonmetal elements. Specifically, examples of ceramics include crystalline silica, silicon carbide, boron nitride, silicon nitride, aluminum nitride, aluminum oxide, magnesium oxide, zinc oxide, titanium carbide, and titanium oxide. Examples of conductive carbon materials include carbon fibers, carbon nanotubes, carbon nanofibers, carbon nanocoils, carbon nanotwists, carbon nanohorns, fullerenes, graphene, diamond, graphite, and carbon black. The thermally conductive filler is used alone or in combination of two or more types.

[0074] The individual shape of the thermally conductive filler is not particularly limited as long as it is "particulate" as a whole. In the present invention, "particulate" refers to an aggregate of multiple solids (interpreted as "particles"), and the individual particles may be in contact with each other or may be separated from each other.

[0075] The thermally conductive filler may be, for example, spherical, fibrous, or scaly. Among them, fibrous thermally conductive fillers are preferred. A small amount of fibrous thermally conductive fillers can also easily improve thermal conductivity. When the amount of thermally conductive filler is small, it is easy to suppress the thermally conductive filler from falling off from the thermally conductive sheet. Therefore, fibrous thermally conductive fillers are particularly suitable for semiconductor manufacturing equipment. Spherical thermally conductive fillers are preferred because they are easily dispersed in the fluorine-containing elastomer. The spherical thermally conductive fillers have an aspect ratio of 1 or more and less than 2. The fibrous or scaly thermally conductive fillers have an aspect ratio of, for example, 2 or more, preferably 30 or more.

[0076] The average length of the fibrous thermally conductive filler is not particularly limited. The length of the fibrous thermally conductive filler may be, for example, 1 μm or more and 1000 μm or less, preferably 5 μm or more and 600 μm or less, and more preferably 50 μm or more and 600 μm or less. The diameter of the fibrous thermally conductive filler is not particularly limited. The diameter of the cross section along the circumferential direction of the fibrous thermally conductive filler may be, for example, 2 nm or more and 150 nm or less, and preferably 5 nm or more and 80 nm or less. The length and diameter of the fibrous thermally conductive filler are the average values ​​of 20 samples measured by a scanning electron microscope (SEM or FE-SEM) or a transmission electron microscope (TEM).

[0077] The fibrous thermally conductive filler is preferably a fibrous carbon material, such as carbon fiber, carbon nanotube, carbon nanofiber, carbon nanocoil, carbon nanotwist, or carbon nanohorn.

[0078] Among these, carbon nanotubes (CNTs) are preferred. CNTs may be single-walled carbon nanotubes (SWNTs), double-walled carbon nanotubes (DWNTs) or multi-walled carbon nanotubes (MWNTs).

[0079] CNTs can be produced by conventional manufacturing methods, such as vapor phase growth methods such as catalytic hydrogen reduction of carbon dioxide, arc discharge, laser evaporation, and CVD, vapor phase flow methods, the HiPco method in which carbon monoxide is reacted with an iron catalyst at high temperature and pressure to grow CNTs in the vapor phase, and the oil furnace method.

[0080] The average particle size of the spherical thermally conductive filler is not particularly limited. The average particle size of the spherical thermally conductive filler may be, for example, 10 nm or more and 1000 nm or less, and preferably 20 nm or more and 300 nm or less. The average particle size is the 50% average particle size (D50) in the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device.

[0081] The spherical thermally conductive filler is preferably carbon black, such as furnace black, acetylene black, or ketjen black.

[0082] The amount of the thermally conductive filler supported on the resin sheet may be 0.01% by mass or more, preferably 0.5% by mass or more, and more preferably 1% by mass or more of the resin sheet. The amount of the thermally conductive filler supported on the resin sheet may be 50% by mass or less, preferably 30% by mass or less, and more preferably 10% by mass or less of the resin sheet.

[0083] The amount of the thermally conductive filler dispersed in the fluorine-containing elastomer may be, for example, 1 part by mass or more, preferably 2 parts by mass or more, and more preferably 10 parts by mass or more, per 100 parts by mass of the fluorine-containing elastomer. The amount of the thermally conductive filler dispersed in the fluorine-containing elastomer may be 150 parts by mass or less, preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and more preferably 30 parts by mass or less, per 100 parts by mass of the fluorine-containing elastomer.

[0084] Fig. 1 is a cross-sectional view showing a thermally conductive sheet according to one embodiment, Fig. 2 is a cross-sectional view showing a thermally conductive sheet according to another embodiment, and Fig. 3 is a cross-sectional view showing an enlarged portion of the thermally conductive sheet according to one embodiment.

[0085] Each of the thermally conductive sheets 10A and 10B comprises a resin sheet 11 having voids, a fluorine-containing elastomer 12 disposed inside the voids, and a thermally conductive material (thermally conductive filler in the illustrated embodiment) 13. The resin sheet 11 is a nonwoven fabric composed of a plurality of fibers 111. The thermally conductive material (thermally conductive filler) 13 contains carbon nanotubes 131 and carbon black 132. The carbon nanotubes 131 are supported by the fibers 111. The carbon black 132 is dispersed in the fluorine-containing elastomer 12.

[0086] An elastomer region 10a is disposed on one main surface 10X side of the thermally conductive sheet 10A in Fig. 1. The elastomer region 10a includes a fluorine-containing elastomer 12 disposed so as to cover the main surface 10X of the resin sheet 11, but does not include the resin sheet 11. The elastomer region 10a may include a thermally conductive material. The thickness tx of the elastomer region 10a is, for example, about 1 / 5 of the thickness of the entire thermally conductive sheet.

[0087] The thermally conductive sheet 10B in Fig. 2 has the same configuration as the thermally conductive sheet 10A, except that the elastomer regions 10a are arranged on both main surfaces 10X and 10Y. The thicknesses tx and ty of each of the elastomer regions 10a are, for example, about 1 / 6 of the thickness of the entire thermally conductive sheet. The thicknesses tx and ty may be about the same or different.

[0088] [Method of manufacturing thermally conductive sheets] The thermally conductive sheet according to this embodiment is manufactured by a method including, for example, a step of preparing a resin sheet having voids (preparation step), a step of retaining a fluorine-containing elastomer in the voids of the resin sheet (retention step), and a step of press-molding the resin sheet retaining the fluorine-containing elastomer (pressing step).

[0089] In the preparation step, a resin sheet carrying a thermally conductive filler may be prepared. In the holding step, a fluorine-containing elastomer having a thermally conductive filler dispersed therein may be used.

[0090] An example of a method for producing a thermally conductive sheet will be described below. Fig. 4 is a flow chart showing the method for producing a thermally conductive sheet according to this embodiment.

[0091] (1) Preparation process (S11) A resin sheet having voids is prepared. The details of the resin sheet are as described above.

[0092] In order to improve the adhesion between the resin sheet and the thermally conductive filler and / or the fluorine-containing elastomer, the resin sheet may be subjected to a silane coupling treatment, a plasma treatment, etc. A thermally conductive material may be added to the inside of the resin sheet.

[0093] The method of supporting the thermally conductive filler on the resin sheet is not particularly limited, and can be obtained, for example, by coating the resin sheet with a dispersion in which the thermally conductive filler is dispersed, or by immersing the resin sheet in a dispersion in which the thermally conductive filler is dispersed. Immersion in the dispersion may be performed multiple times. Coating of the dispersion may be performed on one side of the resin sheet, or may be performed on both sides. Thereafter, the resin sheet is dried. The drying method is not particularly limited, and may be heat drying, vacuum drying, or the like.

[0094] Hereinafter, the supporting step will be specifically described by taking as an example a method for supporting carbon nanotubes on the surface of a resin sheet, but the supporting step according to this embodiment is not limited thereto.

[0095] First, carbon nanotubes are dispersed in a solvent to prepare a carbon nanotube dispersion. The solvent is not particularly limited. Examples of the solvent include water; alcohol-based solvents such as ethanol, n-butyl alcohol, isopropyl alcohol, and ethylene glycol; ester-based solvents such as ethyl acetate; ether-based solvents such as diethyl ether and dimethyl ether; ketone-based solvents such as methyl ethyl ketone, acetone, diethyl ketone, methyl propyl ketone, and cyclohexanone; aliphatic hydrocarbon-based solvents such as hexane and heptane; aromatic hydrocarbon-based solvents such as toluene and benzene; and chlorinated hydrocarbon-based solvents such as dichloromethane, chloroform, and chlorobenzene. These are used alone or in combination of two or more. Among them, ketone-based solvents are preferred.

[0096] The amount of the solvent is not particularly limited. In terms of making it easy to uniformly disperse the carbon nanotubes in the solvent, the amount of the solvent is preferably 20,000 parts by mass or more and 1,000,000 parts by mass or less, more preferably 30,000 parts by mass or more and 300,000 parts by mass or less, and particularly preferably 50,000 parts by mass or more and 200,000 parts by mass or less, relative to 100 parts by mass of the carbon nanotubes.

[0097] A dispersant may be added to the carbon nanotube dispersion. The dispersant is not particularly limited. Examples of dispersants include acrylic dispersants, synthetic polymers such as polyvinylpyrrolidone and polyaniline sulfonic acid, DNA, peptides, and organic amine compounds. These are used alone or in combination of two or more. The amount of dispersant added is appropriately set depending on the type and amount of carbon nanotubes, solvent, and dispersant. The amount of dispersant added is, for example, preferably 100 parts by mass or more and 6,000 parts by mass or less, more preferably 200 parts by mass or more and 3,000 parts by mass or less, and particularly preferably 300 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of carbon nanotubes.

[0098] Next, a resin sheet is immersed in the carbon nanotube dispersion liquid. The resin sheet is then dried, so that the carbon nanotubes are supported on the resin sheet. Drying conditions are not particularly limited and are appropriately set depending on the type and amount of the carbon nanotubes and the solvent.

[0099] (2) Holding process (S12) The fluorine-containing elastomer is held in the voids of the resin sheet. This integrates the resin sheet and the fluorine-containing elastomer. All of the voids in the resin sheet may be filled with the fluorine-containing elastomer, or only a part of the voids in the resin sheet may be filled with the fluorine-containing elastomer.

[0100] (2a) Preparation of elastomer composition First, an elastomer composition containing a fluorine-containing elastomer is prepared. The elastomer composition is prepared, for example, by mixing a fluorine-containing elastomer, a crosslinking agent, other additives, and a solvent. The elastomer composition may be prepared by sequentially adding components such as a fluorine-containing elastomer to a solvent and mixing them, or by mixing components other than the solvent and then mixing the resulting mixture with the solvent. The elastomer composition may also be prepared by mixing a commercially available compound containing a fluorine-containing elastomer, a crosslinking agent, and other additives with a solvent. The mixing is performed, for example, using a known kneader, kneading roll, or mixer. In the elastomer composition, the fluorine-containing elastomer may be dissolved, dispersed, or suspended in the solvent.

[0101] The solvent is not particularly limited, and is appropriately selected depending on the type of fluorine-containing elastomer and the properties of the elastomer composition. Examples of the solvent include aliphatic, aromatic, alcohol, ester, ether, and halogen organic solvents. These are used alone or in combination of two or more. The amount of the solvent added is not particularly limited, and is appropriately set depending on the method of retention, the properties and viscosity of the elastomer composition, etc.

[0102] The viscosity of the elastomer composition is not particularly limited and is appropriately set depending on the holding method, the thickness of the resin sheet, etc. The viscosity of the elastomer composition measured with a B-type viscometer at 20°C may be, for example, about 50 mPa·s or more and 50,000 mPa·s or more.

[0103] The crosslinking agent is not particularly limited and is appropriately selected depending on the composition of the fluorine-containing elastomer, etc. Examples of the crosslinking agent include polyamine compounds such as hexamethylenediamine carbamate and N,N'-dicinnamylidene-1,6-hexamethylenediamine, polyhydroxy compounds such as 2,2-bis(4-hydroxyphenyl)propane and 2,2-bis(4-hydroxyphenyl)perfluoropropane, and organic peroxides such as 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane and 2,5-dimethylhexane-2,5-dihydroperoxide.

[0104] The amount of the crosslinking agent is not particularly limited and may be, for example, from 0.01 to 10 parts by mass, and preferably from 0.1 to 5 parts by mass, per 100 parts by mass of the fluorine-containing elastomer.

[0105] The elastomer composition may contain a crosslinking accelerator as necessary. The crosslinking accelerator is not particularly limited. Examples of the crosslinking accelerator include onium compounds. Examples of the onium compounds include ammonium compounds such as quaternary ammonium salts, phosphonium compounds such as quaternary phosphonium salts, oxonium compounds, sulfonium compounds, cyclic amines, and monofunctional amine compounds.

[0106] The amount of the crosslinking accelerator to be blended is not particularly limited, and may be, for example, from 0.01 to 8 parts by mass, and preferably from 0.02 to 5 parts by mass, per 100 parts by mass of the fluorine-containing elastomer.

[0107] The elastomer composition may contain a crosslinking aid as necessary. The crosslinking aid is not particularly limited. Examples of the crosslinking aid include triallyl cyanurate, trimethallyl isocyanurate, triallyl isocyanurate (TAIC), triacrylformal, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalate amide, triallyl phosphate, bismaleimide, fluorinated triallyl isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl)-1,3,5-trimethylsilyl) and tetramethylsilyl. triazine-2,4,6-trione), tris(diallylamine)-S-triazine, triallyl phosphite, N,N-diallylacrylamide, 1,6-divinyldodecafluorohexane, hexaallyl phosphoramide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylmalonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, tri(5-norbornene-2-methylene) cyanurate, and triallyl phosphite. Among these, TAIC is preferred because of its excellent crosslinkability and physical properties as a heat dissipation material.

[0108] The amount of the crosslinking aid is not particularly limited and may be, for example, 0.01 to 10 parts by mass, preferably 0.1 to 5.0 parts by mass, per 100 parts by mass of the fluorine-containing elastomer.

[0109] The elastomer composition may, if necessary, be blended with usual additives that are blended into fluorine-containing elastomer compositions, such as additives other than thermally conductive fillers (barium sulfate, etc.), processing aids (wax, etc.), plasticizers, colorants, stabilizers, adhesion aids, release agents, conductivity imparting agents, surface anti-tacky agents, flexibility imparting agents, heat resistance improving agents and flame retardants.

[0110] The fluorine-containing elastomer having a thermally conductive filler dispersed therein can be obtained, for example, by adding and mixing the thermally conductive filler together with components such as the fluorine-containing elastomer when preparing an elastomer composition.

[0111] (2b) Applying the elastomer composition to the resin sheet Next, the elastomer composition is applied to the resin sheet. The method of application is not particularly limited, and the elastomer composition may be coated on the resin sheet or the resin sheet may be immersed in the elastomer composition. According to the coating method, an elastomer region is easily formed on the surface of the resin sheet.

[0112] The coating of the elastomer composition may be performed on one side or both sides of the resin sheet. The immersion method is not particularly limited, and a vacuum impregnation method performed under vacuum or a vacuum pressure impregnation method performed while applying pressure under vacuum may be used.

[0113] Thereafter, the resin sheet is dried, whereby the fluorine-containing elastomer is retained in the voids of the resin sheet. The drying method is not particularly limited, and may be heat drying, vacuum drying, or the like.

[0114] (3) Pressing process (S13) The resin sheet holding the fluorine-containing elastomer is press-molded to obtain a thermally conductive sheet having a desired thickness.

[0115] Usually, even if a fluorine-containing elastomer alone is press-molded into a sheet, the thickness of the sheet is likely to vary. Therefore, it is difficult to make the sheet thinner. The variation in thickness of a sheet formed from a fluorine-containing elastomer becomes more noticeable as the sheet becomes larger and thinner.

[0116] By using a resin sheet, the fluorine-containing elastomer can be molded into a sheet having a uniform thickness by press molding, and in particular, a thin and even large sheet can be obtained.

[0117] In the pressing step, the fluorine-containing elastomer may be crosslinked. The conditions of the pressing step are not particularly limited and may be appropriately set in consideration of the crosslinking conditions of the fluorine-containing elastomer. The fluorine-containing elastomer is crosslinked, for example, by heating at a temperature of 150°C to 300°C for 1 minute to 24 hours. After the pressing step, a step of crosslinking the fluorine-containing elastomer may be carried out.

[0118] The obtained thermally conductive sheet is cut, drilled, etc., as necessary, and then mounted on various devices and electronic devices. According to the manufacturing method of this embodiment, a uniform, thin, and large-area thermally conductive sheet can be obtained, resulting in a high yield and being applicable to various uses. The thermally conductive sheet is particularly suitable for use in semiconductor manufacturing equipment. EXAMPLES

[0119] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are by weight unless otherwise specified. The number of parts mixed is the mass of the solid content.

[0120] [Example 1] (i) Preparation of resin sheet PTFE nonwoven fabric (R-250 manufactured by Tomoegawa Paper Co., Ltd., porosity 65%, mass per unit area 190g / m 2 A fiber with a diameter of 35.2 μm and a thickness of 0.25 mm was prepared.

[0121] (ii) Preparation of Elastomer Composition A mixture was obtained containing 100 parts of a fluorine-containing elastomer (TFE / perfluoro(methyl vinyl ether) / cyano group-containing monomer = 59.4 / 40.1 / 0.5 (molar ratio), heat resistance temperature in compression set test of 300°C, heat resistance temperature in TG method of 420°C, manufactured by Daikin Industries, Ltd.), 0.8 parts of a crosslinking agent (4,4'-[2,2,2-trifluoro-1-(trifluoromethyl)ethylidene]bis[N1-phenyl-1,2-benzenediamine]), and 23 parts of a thermally conductive filler (carbon black, manufactured by Cancarb Corporation's Thermax N990, D50: 280 nm). An organic solvent (FC770, manufactured by 3M) was mixed with this mixture to prepare an elastomer composition with a concentration of 4 mass% (viscosity 150 mPa s).

[0122] (iii) Step of retaining the elastomer composition on a resin sheet The above-mentioned elastomer composition was applied to one surface of a PTFE nonwoven fabric using a film applicator. After that, it was dried at 80°C for 12 hours to hold the elastomer composition inside the voids on one surface side of the PTFE nonwoven fabric. Then, in the same manner as above, the elastomer composition was held in the voids on the other surface side of the PTFE nonwoven fabric.

[0123] (iv) Press molding The PTFE nonwoven fabric holding the elastomer composition was placed in a 200 mm x 200 mm mold and subjected to a load of 45 kgf / cm 2 The sheet was press molded at 180° C. for 30 minutes. A thermally conductive sheet A1 was thus obtained. An evaluation sample a1 measuring 100 mm×100 mm was cut out from the thermally conductive sheet A1.

[0124] The proportion of the fluorine-containing elastomer in the thermally conductive sheet A1 was 49.4% by mass. The total amount of the thermally conductive material was 11.4% by mass of the thermally conductive sheet A1. Elastomer regions (each having a thickness of 53 to 59 μm) were formed on both sides of the thermally conductive sheet A1. The heat resistance temperature of the thermally conductive sheet A1 was 420°C in the TG method.

[0125] [Example 2] A thermally conductive sheet A2 and an evaluation sample a2 (100 mm x 100 mm) thereof were obtained in the same manner as in Example 1, except that in the elastomer composition retaining step (iii) of Example 1, the elastomer composition was applied only to one surface of the PTFE nonwoven fabric.

[0126] The ratio of the fluorine-containing elastomer in the obtained thermally conductive sheet A2 was 45.7% by mass. The total amount of the thermally conductive material was 10.5% by mass of the thermally conductive sheet A2. An elastomer region (thickness 110 μm) was formed on one side of the thermally conductive sheet A2. The heat resistance temperature of the thermally conductive sheet A2 in the TG method was 420°C.

[0127] [Example 3] A thermally conductive sheet A3 and an evaluation sample a3 (100 mm x 100 mm) thereof were obtained in the same manner as in Example 2, except that a PTFE nonwoven fabric carrying CNTs was used instead of the PTFE nonwoven fabric of Example 2. The heat resistance temperature of the thermally conductive sheet A3 in the TG method was 420°C.

[0128] The resin sheet was obtained by immersing the PTFE nonwoven fabric used in Example 2 in a dispersion containing CNTs (carbon nanotubes, Taiyo Nippon Sanso Corporation, CNT powder grade DL, diameter of cross section along the circumferential direction 5 nm to 20 nm, length 150 μm to 600 μm), and then drying. The amount of CNTs supported was 1.1 mass % of the PTFE nonwoven fabric before support.

[0129] The proportion of the fluorine-containing elastomer in the thermally conductive sheet A3 was 48.3 mass%. The total amount of the thermally conductive material was 11.1 mass% of the thermally conductive sheet A3. An elastomer region (thickness 98 μm) was formed on one side of the thermally conductive sheet A3.

[0130] [Comparative Example 1] A thermally conductive sheet B1 and its evaluation sample b1 (100 mm x 100 mm) were obtained in the same manner as in Example 1, except that no resin sheet was used. However, during press molding (4), the fluorine-containing elastomer could not spread to the corners of the 200 mm x 200 mm mold. The size of the obtained thermally conductive sheet B1 was about 170 mm x 180 mm. The heat resistance temperature of the thermally conductive sheet B1 in the TG method was 420°C.

[0131] [evaluation] The following evaluations were carried out on the evaluation samples a1 to a3 and b1 obtained in Examples 1 to 3 and Comparative Example 1. The results are shown in Table 1.

[0132] (a) Thickness measurement The thickness of the evaluation sample was measured at five points. The measurement points were near the four corners (points a to d in a clockwise direction) and at the center (point e), and were 3 cm or more apart. The average and standard deviation of the measurements were calculated.

[0133] (b) Measurement of adhesion to other components A test piece measuring 50 mm x 50 mm was cut out from the evaluation sample. This test piece was compressed with a SUS304 plate and heated at 250°C for 16 hours. After cooling to room temperature, the thermal conductive sheet and the SUS304 plate were peeled off. The force required for peeling was measured using a universal testing machine (HIT-L, manufactured by Japan Measurement Systems Co., Ltd.).

[0134] (c) Measurement of thermal conductivity The thermal conductivity was calculated by multiplying the thermal diffusivity of the evaluation sample by the specific heat of the evaluation sample obtained by the DSC method and the density of the evaluation sample obtained by the Archimedes method. The thermal diffusivity was measured using a laser flash method under the following conditions.

[0135] (Thermal diffusivity) Measuring equipment: ULVAC-RIKO TC-7000 Method for determining thermal diffusivity: Half-time method Measurement temperature: room temperature 25℃

[0136] (d) Conductivity measurement Conductivity is 1.00 x 10 -4 If it is less than S / m, it is 1.00×10 according to JIS K 6911. -4 When the resistivity was S / m or more, the electrical resistivity of the evaluation sample was measured in accordance with JIS K 7194. The electrical conductivity was calculated from the electrical resistivity.

[0137] (e) Hardness measurement The Martens hardness of both surfaces of the evaluation sample was measured by the nanoindentation method according to ISO 14577. Specifically, an indenter was pressed into both surfaces of the evaluation sample with a load of 10 mN. The Martens hardness was obtained from the indentation depth.

[0138] [Table 1]

[0139] The thermally conductive sheets A1, A2, and A3 of Examples 1 to 3 are thin and uniform in thickness. On the other hand, since no resin sheet was used in Comparative Example 1, the thermally conductive sheet B1 obtained was thick overall and had a large variation in thickness.

[0140] Thermally conductive sheets A1, A2, and A3 having the resin sheets of Examples 1 to 3 had a smaller adhesive strength to other members than thermally conductive sheet B1 of Comparative Example 1. In particular, the adhesive strength of thermally conductive sheets A2 and A3 having an elastomer region only on one side of Examples 2 and 3 was small. In other words, thermally conductive sheets A1, A2, and A3 have excellent peelability, so that the thermally conductive sheets can be removed smoothly while suppressing the generation of residues.

[0141] The thermally conductive sheet A3 of Example 3 had a large total amount of thermally conductive filler, and furthermore, the thermally conductive filler was supported on the resin sheet, and therefore exhibited the highest thermal conductivity and electrical conductivity.

[0142] The thermally conductive sheets A1, A2, and A3 of Examples 1 to 3 all have a low Martens hardness on the surface having the elastomer region, which is expected to improve the adhesion between the thermally conductive sheet and the heat generating body and / or heat dissipating body and thus improve the thermal conductivity. [Industrial Applicability]

[0143] The thermally conductive sheet of the present invention has high thermal conductivity and high heat resistance, and therefore can be suitably used in semiconductor manufacturing equipment. [Explanation of symbols]

[0144] 10A, 10B Thermally conductive sheet 10X, 10Y main surface 10a Elastomer region 11 Resin sheet (non-woven fabric) 111 Textiles 12 Fluorine-containing elastomers 13 Thermally conductive materials (thermally conductive fillers) 131 Carbon Nanotubes 132 Carbon Black

Claims

1. A resin sheet having voids; a fluorine-containing elastomer disposed at least inside the void; a thermally conductive material; the fluorine-containing elastomer is further disposed so as to cover at least a portion of at least one main surface of the resin sheet, A thermally conductive sheet having a thickness of 0.05 mm or more and 0.5 mm or less.

2. the thermally conductive material comprises a particulate thermally conductive material; The thermally conductive sheet according to claim 1 , wherein at least a portion of the particulate thermally conductive material is supported on the resin sheet.

3. The thermally conductive sheet according to claim 1 , wherein the resin sheet contains a resin material having a heat resistance temperature of 150° C. or higher.

4. The thermally conductive sheet according to any one of claims 1 to 3, wherein the resin sheet is a fiber structure.

5. The thermally conductive sheet according to any one of claims 1 to 4, wherein the thermally conductive material comprises a fibrous carbon material.

6. The thermally conductive sheet according to any one of claims 1 to 5, wherein the fluorine-containing elastomer is further arranged so as to cover one main surface of the resin sheet.

7. The thermally conductive sheet according to any one of claims 1 to 5, wherein the fluorine-containing elastomer is further arranged so as to cover both main surfaces of the resin sheet.

8. The thermally conductive sheet according to any one of claims 1 to 7, wherein the standard deviation of thickness at any five points on the thermally conductive sheet is 0.020 or less.

9. The thermally conductive sheet according to any one of claims 1 to 8, wherein the resin sheet is formed from a resin material containing a fluororesin.

10. The thermally conductive sheet according to any one of claims 1 to 9, which is used in a semiconductor manufacturing device.

11. Providing a resin sheet having voids; retaining a fluorine-containing elastomer in the voids of the resin sheet; and a step of press-molding the resin sheet holding the fluorine-containing elastomer to obtain a thermally conductive sheet, At least one of the resin sheet and the fluorine-containing elastomer has a thermally conductive material, the fluorine-containing elastomer is disposed so as to cover inside voids of the resin sheet and at least a part of at least one of the main surfaces of the resin sheet, The method for producing a thermally conductive sheet, wherein the thermally conductive sheet has a thickness of 0.05 mm or more and 0.5 mm or less.

12. The method for producing a thermally conductive sheet according to claim 11 , wherein in the step of preparing a resin sheet, the resin sheet carrying particulate thermally conductive material is prepared.

Citation Information

Patent Citations

  • Thermally conductive sheet

    JP2002038033A

  • Electrostatic chuck

    JP2004140056A

  • Sheet for adsorption

    JP2012148236A

  • Thermal conductive composition and thermal conductive sheet obtained by treating the same

    JP2013023664A

  • Heat conductive sheet

    JP2014061617A